Active and passive voice in Bulungan Language (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
Bulungan Language as one of the langugaes in North Kalimantan Province has scattered speakers in 8 sub-districts. As language with scattered speakers made Bulungan Language get less attention from language researcher dan linguist to describe it thoroughly. Bulungan language has active voice and passive voice as part of its grammar which has not been studied furtherly yet. Then, the rseracher take this chance to discuss active voice and passive voice in the Bulungan language in this study. This research employed qualitative descriptive research. The data used in this study was oral data directly taken from the native Bulungan speakers. The data collection technique used in this study was by listening technique and the note-taking technique. This study revealed that the active and passive voice of the Bulungan language had different markers but same passive voice property across languages.